2015
DOI: 10.1038/srep17646
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Characterisation of the System Effects of Aristolochic Acid: A Novel Joint Network Analysis towards Therapeutic and Toxicological Mechanisms

Abstract: Aristolochic acid (AA) is the major active component of medicinal plants from the Aristolochiaceae family of flowering plants widely utilized for medicinal purposes. However, the molecular mechanisms of AA systems effects remain poorly understood. Here, we employed a joint network analysis that combines network pharmacology, a protein–protein interaction (PPI) database, biological processes analysis and functional annotation analysis to explore system effects. Firstly, we selected 15 protein targets (14 genes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Previous in vivo work showed that Nf-κb and members of its pathway are upregulated in AAI-exposed kidneys [29]. NF-κB also plays a role in the inflammatory response associated with AAN [63]. Overall, these findings may indicate that a Trp53(-/-) genotype confers a survival advantage to AAI-exposed renal cells and/or an inflammatory response is initiated in injured Trp53(-/-) kidneys.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous in vivo work showed that Nf-κb and members of its pathway are upregulated in AAI-exposed kidneys [29]. NF-κB also plays a role in the inflammatory response associated with AAN [63]. Overall, these findings may indicate that a Trp53(-/-) genotype confers a survival advantage to AAI-exposed renal cells and/or an inflammatory response is initiated in injured Trp53(-/-) kidneys.…”
Section: Discussionmentioning
confidence: 74%
“…AAN is characterised by fibrosis [62], thus it could be postulated that AAI contributes to this phenomenon by inducing EMT. In fact, previous studies showed that AAI-induced upregulation of transforming growth factor β (TGF-β), which acts on EMT pathways, contributes to the formation of renal fibrosis in AAN [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This integrative approach can be easily applied as a new approach methodology (NAM) ( Bopp et al 2019 ), which may offer support to methods alternative to animal testing or to identify biological pathways that require more focused laboratory study. Previous studies have demonstrated that systems chemical toxicology models combined with computational network biology may help in understanding chemical toxicity in humans ( Hartung et al 2017 ; Nie et al 2015 ; Taboureau and Audouze 2017 ). Our tripartite network supports the notion that exposure to EDCs may contribute to aggravation of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous methods, systems pharmacology provides an integrated “systems-level” approach to determi-ning mechanisms of action of drugs in animal models and in patients28. Systems pharmacology is widely used in drug discovery, target prediction and mechanism research, especially in traditional herbal medicine3132. This article applies systems pharmacology to investigate the mechanism of berberine and its interaction with other clinical drugs in treating PCOS at the target level.…”
mentioning
confidence: 99%